Titanium trisulfide nanosheets and nanoribbons for field emission- based nanodevices - Pawbake, Amit S.; Khare, Ruchita T.; Island, Joshua O.; Flores, Eduardo; Ares, Jose R.; Sanchez, Carlos; Ferrer, Isabel J.; Pawar, Mahendra; Frank, Otakar; More, Mahendra A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; et al. (ACS Applied Nano Materials, 2023)
The field emission (FE) properties of TiS3 nanosheets and nanoribbons, synthesized by direct sulfuration of bulk titanium, are investigated. The nanosheets show an enhanced FE behavior with a low turn-on field of similar to 0.3 V/ mu m, required for drawing an emission current density of similar to 10 mu A/cm2. Interestingly, the TiS3 nanosheet emitter delivered a large emission current density of similar to 0.9 mA/ cm2 at a relatively low applied electric field of similar to 0.4 V/mu m. We have estimated the values of the field enhancement factor (beta), which are found to be similar to 5 x 104 for the TiS3 nanosheet emitter and similar to 4 x 103 for the nanoribbon emitter. We attribute the superior FE performance to the presence of atomically sharp edges and the reduced thickness of TiS3, as reflected in the high value of beta. In fact, the nanosheet sample presents a higher density of ultrathin layers (similar to 12 nm-thick), and thus, they have a larger edge to volume ratio than the nanoribbon samples (which are similar to 19 nm-thick). The superior FE behavior of TiS3 nanosheets over nanoribbons makes them a propitious field emitter and can be utilized for various FE-based applications, demanding large emission currents and lower operational voltages. Moreover, the FE current stability recorded on these samples confirms their promising performance. Thus, the present investigation brings out a great promise of TiS3 nanosheets and nanoribbons as field emitters for vacuum nanoelectronics devices.
Keywords: Current stability; field emission; nanoribbon; nanosheets; TiS3